2013
DOI: 10.2119/molmed.2013.00013
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin (EPO) Increases Myelin Gene Expression in CG4 Oligodendrocyte Cells through the Classical EPO Receptor

Abstract: Erythropoietin (EPO) has protective effects in neurodegenerative and neuroinflammatory diseases, including in animal models of multiple sclerosis, where EPO decreases disease severity. EPO also promotes neurogenesis and is protective in models of toxic demyelination. In this study, we asked whether EPO could promote neurorepair by also inducing remyelination. In addition, we investigated whether the effect of EPO could be mediated by the classical erythropoietic EPO receptor (EPOR), since it is still questione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 39 publications
5
37
0
Order By: Relevance
“…Schwann cells express a receptor for EPO, which may be responsible for the beneficial effects of EPO administration . EPO stimulates Schwann cell migration, and its administration has been shown to have a positive effect on myelination . These beneficial effects of EPO on myelination have already been translated into clinical trials for demyelinating diseases such as multiple sclerosis and amyotrophic lateral sclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells express a receptor for EPO, which may be responsible for the beneficial effects of EPO administration . EPO stimulates Schwann cell migration, and its administration has been shown to have a positive effect on myelination . These beneficial effects of EPO on myelination have already been translated into clinical trials for demyelinating diseases such as multiple sclerosis and amyotrophic lateral sclerosis .…”
Section: Discussionmentioning
confidence: 99%
“…RNA quality and concentration were determined using NanoDrop ND-1000 (NanoDrop Technologies, Thermo Fisher Scientific, Waltham, MA, USA) 20. Reverse transcription and real-time qPCR for EPOR, βCR, VEGF, and β2-microglobulin (a housekeeping gene not affected by changes in O 2 levels) were carried out on RNA samples using Taqman gene expression assays (Thermo Fisher Scientific) as previously reported 20,21. For gene expression quantification, the comparative threshold cycle (ΔΔCt) method was used following the guidelines of Thermo Fisher Scientific.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, EPO‐mediated functional improvement can be demonstrated from single doses up to days after injuries in mice and seems to correlate with injury (Elfar et al, ). Although the mechanisms by which EPO works are still poorly understood, it is thought to work by promoting the expression of myelin genes, MPZ and PMP22 (Cervellini et al, ). We have shown that mice which received systemic EPO following nerve crush injury maintained more myelinated axons at the site of injury (Sundem et al, ).…”
Section: Erythropoietinmentioning
confidence: 99%